The relationship between conflicts and employee performance at Jabatan Belia dan Sukan Johor / Nurazela Ngadiman - Ngadiman, Nurazela (2014)
This study is about the relationship between conflict and employee performance at Jabatan Belin Dan Sukan, Johor (JBSJ). The purpose of this study is to identify the most type of conflict that influences the employee performance at JBSJ. This study also wants to investigate the level or employee performance at JBSJ. Other than that, this study also wants to identify the relationship between conflict and employee performance. The data gathered through the questionnaire distributed to the employee at Jabatan Belia Dan Sukan Johor and 30 respondents were chosen randomly and to determine the relationship conflicts and employee performance at JBSJ.